Modification of the surface layers of copper by a diffuse discharge in atmospheric pressure air; Proceedings of SPIE; Vol. 9810 : Atomic and Molecular Pulsed Lasers XII - Shulepov M. A. Mikhail; Erofeev M. V. Mikhail Vladimirovich; Oskomov K. V. Konstantin; Tarasenko V. F. Victor Fedotovich (Laser Systems and New Laser and Optical Technologies, Laser Applications, 2015)
Title screen